Causes of open fractures: orthopaedic injuries related to home-made agricultural vehicles in the eastern Black Sea region of Turkey - Say, Ferhat; Coşkun, Hüseyin Sina; Erdoğan, Murat; Bülbül, Ahmet Murat; Gürler, Deniz (Tubitak Scientific & Technical Research Council Turkey, 2016)
Background/aim: Small vehicles known locally as pat-pats, which are used in agricultural work, are forbidden in traffic. The inherent instability of the vehicle may result in accidents, both on farmland and in traffic. The aim of this study was to evaluate orthopaedic injuries related to pat-pats. Materials and methods: Patients hospitalised for pat-pat accidents in two central hospitals in Samsun between December 2006 and October 2013 were scanned using ICD codes. A total of 46 patients with orthopaedic injuries (43 male, 3 female) with a mean age of 36 ± 13.3 years were evaluated. Results: The most injured age group was between 10 and 49 years (n = 40, 87%), and accidents occurred most in summer (n = 30, 65%). Open fractures were determined in 42 (91%) patients. Amputation was necessary in 4 (8%) patients. The hospitalisation period was a mean of 17.1 ± 14 days. A statistically significant relationship was determined between open fracture type and the hospitalisation period (P < 0.001). Conclusion: As most of the orthopaedic injuries related to home-made agricultural machines are open fractures, it is important to guard against these types of injuries. The regulations that these machines are not used in traffic should be enforced and safer practices should be applied for use in agriculture.
Keywords: Agriculture; Accidents; Open Fractures; Traffic